International review of research in mental retardation. (International review of research in mental retardation ;, 1997)
This serial was established under the editorship of Dr. Norman R. Ellis in 1966. As a result of his editorial effort and the contributions of many authors, the serial is now recognized as the area's best source of reviews of behavioral research on mental retardation. From its inception, active research scientists and graduate students in mental retardation have looked to this serial as a major source of critical reviews of research and theory in the area.